MARKETING STRATEGY TO ENHANCE BRAND AWARENESS FOR COMMERCIAL PRODUCTS OF PERUM BULOG: CASE OF BERASKITA AND DAGINGKITA - Rachmat Komara, Ary
This research will try to raise the issue of marketing strategy of premium rice products (BerasKITA) and buffalo meat (DagingKITA) which are managed commercially by Perum BULOG where the level of brand awareness from the public and the sales level for those two products are still low, and finding the solutions to these problems. In addition to the issue of brand awareness, as is generally known that the name of BULOG is very closely related to rice for middle-low class society or what we commonly known as RASKIN. The image of Perum BULOG seems to have been attached to RASKIN which is identical to the public perception of bad quality of rice. This immediately affects the image of BerasKITA products. While for buffalo meat products, marketing is constrained by the habits of Indonesian people who are accustomed to consuming types of beef and in fresh conditions compared to frozen buffalo meat, even though the selling price of beef is much higher than the price of frozen buffalo meat marketed by Perum BULOG. Regarding to these conditions, researcher will use several analyzes to find out the problem both internally and externally from Perum BULOG. To analyze the external environment where it aims to determine the Opportunity and Threat of BerasKITA and DagingKITA, the research will use Porter 's 5 Forces Analysis. Meanwhile, to analyze the internal environment where it aims to determine the Strenght and Weakness of BerasKITA and DagingKITA, the research will use Diamond Analysis, and Marketing-Mix Analysis. Furthermore, the two results of the above analysis will be combined with the results of qualitative research conducted by researchers in the form of mini interviews and questionnaires, which are expected to be the basis for determining the marketing strategies that are suitable to solve the problems of BerasKITA and DagingKITA. Based on the results of the analysis and qualitative data collection, the researchers recommended marketing strategy by using 9 Cores Element of Marketing that are expected to be the solution to the problems faced by the Perum BULOG of the BerasKITA and DagingKITA as follows: a. Strategy - Segmentation: Families living in urban areas, already have jobs, and with middle to upper economic classes, where the market segment is more accustomed to buying rice and meat in the modern market and tends to buy rice and meat oriented to product quality but still at reasonable prices. - Targeting: Women aged 17 to 35 years old, married, live in JABODETABEK, accustomed to shopping for rice and meat in a modern market with a range of quality products but still at reasonable prices. - Positioning: 1. BerasKITA For women aged 17 to 35 years who are married, live in JABODETABEK, and are accustomed to shopping for rice in the modern market, and oriented to product quality but still at reasonable prices, BerasKITA is a choice of premium rice derived from Indonesian farmers who are processed and packaged using modern machines, free of chemicals and has been standardized ISO 9001, available with various product and packaging variants and offered at a cheaper price than similar products on the market. 2. DagingKITA For women aged 17 to 35 years who are married, live in JABODETABEK, and are accustomed to shopping for meat in modern markets, and oriented to product quality but still at reasonable prices, DagingKITA is a choice of frozen buffalo meat processed and packaged using modern machines. , and with freezing technology through very low minus temperatures (blasting -40oC), processed through the aging process to complete the rigor mortis process which makes meat softer, has been certified Halal from MUI, has a taste and texture similar to beef, but offered at a cheaper price than beef on the market. b. Tactics (Differentiation, Marketing-Mix) - Differentiation: 1. BerasKITA BerasKITA products have more rice variants marketed compared to competitors, besides BerasKITA also has more volume packaging options that make it easier for consumers to buy rice according to their needs. In terms of infrastructure, BerasKITA products are also supported by a variety of processing technologies that make it easier for Perum BULOG to maintain product quality and the availability of warehouses to store large quantities of production. In addition to building technology, Perum BULOG is also supported by the availability of experts in the field of rice procurement, and a quality control team that can always maintain the quality of rice processed and marketed to meet the requirements set by the Perum BULOG. 2. DagingKITA DagingKITA products come from frozen buffalo meat which is processed and packaged using modern machinery. Perum BULOG has also invested in providing cold storage in many places to support the DagingKITA sales network, and is supported by a quality control team that guarantees the quality of DagingKITA products to be marketed. The advantages in the field of infrastructure compared to competitors will immediately make the marketing of Perum BULOG for DagingKITA products broader than the number of marketing places owned by competitors. - Marketing-Mix • Product: 1. BerasKITA BerasKITA products will focus on producing variants of rice that consumers are interested in such as fragrant pandanus, ramos centers, long grain, and rojo lele. Maintaining a variety of packaging volume marketed as an option for consumer convenience. 2. DagingKITA For DagingKITA products, in addition to frozen meat sales, it is also necessary to approach consumers by developing derivative products that can be produced from buffalo meat, such as buffalo meat meatballs, buffalo meat sausages, and buffalo meat burger. The development of processed buffalo meat products is needed to increase consumer consumption interest in buffalo meat, where if the form of the product being marketed is not in the form of whole meat, it is expected to increase consumer interest in trying to consume it. • Price: Maintaining the selling price of BerasKITA and DagingKITA products that are lower than similar products from competitors. • Promotion: Advertise through various media choices such as television, newspapers, brochures, online, and also social media (Instagram, Facebook), where based on the results of qualitative research conducted through a questionnaire the results found that Instagram is currently the most used social media. Perum BULOG must focus more on communicating the most favored products such as in this case BerasKITA and DagingKITA. So that the advertisements made will focus on each product. Furthermore, the promotion of bundling products can also be carried out to further introduce communication and marketing media in the form of mouth to mouth, or from one consumer to another for the quality of BerasKITA and DagingKITA products. Increase the campaign about the buffalo meat product and its benefits, like join the food bazzar or make a stan in several events like Car Free Day (CFD), involve the food blogger, etc. Furthermore, relationships with customers also need to be improved by providing a Customer Relationship Program (CRM) in order to establish an active and good relationship between Perum BULOG and its customers who are expected to have good bonds, minimizing the risk of consumers switching to using other products from competitors. • Place: Based on the results of qualitative analysis it is known that the target market for middle to upper class economic families is more likely to shop in the modern market. In this regard, it is necessary to strengthen marketing distribution and communication in the modern market which includes minimarkets (focus on: Alfamart, Indomaret), supermarkets (focus on: Superindo, Farmers Market), and hypermarkets (focus on: Transmart, Giant, Hypermart, Carrefour) to reach these target markets. However, for market development, penetration can also be done through traditional markets and online stores. It is expected that with the implementation of the above recommendations, it will be able to increase brand awareness of the BerasKITA and DagingKITA in the community, which will certainly be able to increase the sales of both products.